Indigenous practices of vegetable cultivation in Thrissur district - Manju V (Department of Agricultural Extension, College of Horticulture, 1997)
A study on the indigenous practices of vegetables was carried out using 120 vegetable farmers selected from the three vegetable growing blocks of Thrissur district of Kerala state namely Chalakkudy, Wadakkancherry and Puzhakkal. The data were collected with the help of a pre-test structured interview schedule by personally interviewing the respondents selected from three vegetable growing panchayats of the above blocks. The analysis of the data revealed that, out of seventeen selected personal, socio-economic and psychological characteristics of the farmers ten variables were negatively and significantly related with their knowledge on indigenous practices. Of these, maximum variation on knowledge on indigenous practices was caused by two characteristics namely market orientation and information source utilisation of the farmers. Similarly out of these seventeen personal, socio-economic and psychological characteristics of the respondents, twelve characteristics were negatively and significantly related with their extent of adoption of indigenous practices. Of these, maximum variation was contributed by three variables such as farm size, labour input and scientific orientation. The evaluative perception of indigenous practices by farmers and subject matter specialists were separately measured in terms of six selected attributes. The attributes selected were simplicity, profitability, sustainability, efficiency, input availability and flexibility. The results in general indicated that the attributes simplicity, sustainability and profitability of majority of the indigenous practices were perceived as more or less high by the respondents. Emergence of new pests and diseases, increased pests and diseases, low productivity were some of the important constraints perceived by the farmers in the case of indigenous technology adoption.